MULTICRITERION METHODS OF DECISION-MAKING BY THE MILITARY AUTHORITIES - Alexey N. Zagorka; Anatoliy K. Pavlikovsky; Irina A. Zagorka (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni, 2018)
Іn the article the necessity of application of multicriterion methods of analysis is shown during development of military authorities of decision on the operation (battle) of grouping of troops (forces). Requirements are formulated to such methods. The features of application of component criteria are considered, methods of analysis of hierarchies, taxonomy, game and fuzzy sets theories for the choice of method of combat operations of grouping of troops (forces) during development of decision on an operation (battle). The expert estimation of accordance of application of the transferred methods is conducted to the set requirements (account of vagueness of application of methods of combat operations an opponent, decision-making validity on an operation (battle), method testing, adequacy of process of decision-making of intellectual activity of commander (command)). It is suggested for the choice of method of combat actions of grouping of troops (forces) in the conditions of vagueness of situation to apply the methods of game and fuzzy sets theory.